(untitled) (Journal of the College of Basic Education, 2022)
The Husseini councils played an important role in promoting the concept of national unity and confronting the attempts of British colonialism to sow the seeds of discord among the Iraqi people, as religious scholars in the holy city of Kadhimiya confronted the military occupation when it entered Iraq in 1914 AD, and participated in the celebrations of the Prophet’s birthday in the mosques of Baghdad, symbolic of the people’s unity. Al-Kadhimiya scholars also contributed to deterring some pens that tried to distort history and stigmatize Islamic religious symbols. As Sayyid Heba al-Din al-Shahristani is one of the most prominent scholarly figures who spread the enlightened renewal thought and elevate the Husseini rituals, and during his reign they reached the zenith of their political and social action and transformed the pattern of neighborhoods into something similar to an integrated institutional work that involves political, social, cultural, educational and ideological goals. The honorable Sunni community from inside and outside Iraq, to participate in the Ashura commemoration of Imam Hussein, peace be upon him, and to contribute seriously in unifying efforts to close ranks and protect the entity of the state and the interests of its people, drawing from the sacrifices of Imam Hussein, peace be upon him, a sacred humanitarian project to defend the right and justice for the oppressed and sacrifice for the lofty goals of the nation Through poignant poems and words.